2013
DOI: 10.1103/physrevb.88.075414
|View full text |Cite
|
Sign up to set email alerts
|

Full counting statistics of a single-molecule quantum dot

Abstract: We investigate the full counting statistics of a single quantum dot strongly coupled to a local phonon and weakly tunnel-connected to two metallic electrodes. By employing the generalized nonequilibrium Green function method and the Lang-Firsov transformation, we derive an explicit analytical formula for the cumulant generating function, which makes one to be able to identify distinctly the elastic and inelastic contributions to the current and zero-frequency shot noise. We find that at zero temperature, the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 70 publications
0
56
0
Order By: Relevance
“…(33) and (53), respectively, are the main analytical results of this paper 72 . It should be emphasized that only few impurity models, essentially, variants of the single dot Anderson model 18,27,[78][79][80][81] , can be solved analytically, within certain approximations, to provide the CGF and expose charge and energy statistics under interactions. Our work here substantially extends these efforts, by solving the FCS of a vibrationally assisted two-site electronic conduction.…”
Section: A Da-ah Model: Quantum Master Equation Approachmentioning
confidence: 99%
“…(33) and (53), respectively, are the main analytical results of this paper 72 . It should be emphasized that only few impurity models, essentially, variants of the single dot Anderson model 18,27,[78][79][80][81] , can be solved analytically, within certain approximations, to provide the CGF and expose charge and energy statistics under interactions. Our work here substantially extends these efforts, by solving the FCS of a vibrationally assisted two-site electronic conduction.…”
Section: A Da-ah Model: Quantum Master Equation Approachmentioning
confidence: 99%
“…While the stationary transport properties of the AndersonHolstein model have been extensively analyzed [21][22][23][24][25][26], their analysis in the time domain has been much less analyzed [27]. Recent calculations, based on numerically exact methods such as diagrammatic quantum Monte Carlo (diagMC) [28], have indicated that for strong electron-phonon coupling there exists a regime in which different initial conditions lead to different transport properties at short times.…”
Section: Introductionmentioning
confidence: 99%
“…[35]. We also point out that in all the preceding approximations the basic assumption of having a equilibrium phonon distribution was made for the evaluation of the polaron correlators.…”
Section: Dressed Tunneling Approximationmentioning
confidence: 99%
“…[30]. In the opposite regime, the so-called polaronic regime, perturbation theory breaks down and other type of approaches are necessary [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%